Technological accessibility and new frontiers in Boipeba, State of Bahia, Brazil (Research, Society and Development, 2020)
Considered a mechanism to induce social and economic growth and development, information and communication technologies (ICT) have a strong and decisive influence on the way of life of individuals, establishing a new social order in contemporary societies. Despite the understanding of the determinant role of ICT for development in the various spheres of a society, there is still a significant distance to be crossed especially in towns that are geographically remote from large metropolises, such as Boipeba, located in Costa do Dendê, in the Southern of the Brazilian state Bahia. Population with predominantly traditional lifestyle whose dissemination of the Internet occurred recently. This research aims to describe the main changes in the daily lives of residents of Boipeba from the use of this technology. A documentary analysis was carried out through a review of the existing literature on the subjects covered in addition to the application and compilation in the island’s residents. Considering the results obtained, it was possible to conclude that the Internet enabled improvements from an economic perspective such as the dissemination of the island’s tourist attractions and a setback in the social sphere especially in interpersonal relationships.